2007
DOI: 10.1002/hep.21735
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in themethylenetetrahydrofolate reductase andthymidylate synthase genes and risk of hepatocellular carcinoma

Abstract: H epatocellular carcinoma (HCC) is the sixth most common cancer in the world and the third leading cause of cancer deaths. 1 The overall 5-year survival for patients with HCC is less than 10%.Only 30% of patients with HCC are considered candidates for surgical resection; however, the recurrence rate after surgery is approximately 40% to 50%. 2 The major risk factors for HCC vary somewhat with its geographical distribution. Chronic infection with hepatitis B virus (HBV) is by far the most important risk factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 43 publications
1
50
1
1
Order By: Relevance
“…A study conducted by Kuramochi et al suggested that the status of the TS 5 0 -UTR polymorphism was an independent predictive marker for survival benefit from 5-FU-based therapy in esophageal adenocarcinoma patients [31]. A case-control study conducted by Yuan et al showed that individuals with TS 3 0 UTR ins6/del6 or del6/del6 allele had a statistically significant 50% reduction in risk of hepatocellular carcinoma [32]. A case-control study conducted by Wang et al showed that individuals with TS 5 0 UTR 3Rc/3Rc genotype had a statistically significant increased risk of pancreatic cancer [33].…”
Section: Discussionmentioning
confidence: 97%
“…A study conducted by Kuramochi et al suggested that the status of the TS 5 0 -UTR polymorphism was an independent predictive marker for survival benefit from 5-FU-based therapy in esophageal adenocarcinoma patients [31]. A case-control study conducted by Yuan et al showed that individuals with TS 3 0 UTR ins6/del6 or del6/del6 allele had a statistically significant 50% reduction in risk of hepatocellular carcinoma [32]. A case-control study conducted by Wang et al showed that individuals with TS 5 0 UTR 3Rc/3Rc genotype had a statistically significant increased risk of pancreatic cancer [33].…”
Section: Discussionmentioning
confidence: 97%
“…For decades of years, there were a lot of studies explored the relationship of polymorphisms of candidate gene and HCC (Yuan et al 2007;Tanabe et al 2008;Akkiz et al 2009;Imaizumi et al 2009;Ognjanovic et al 2009). Because liver is the largest metabolic organ in human body, the candidate SNPs studied mainly related to the genes encoding carcinogen-metabolising enzymes, such as cytochrome P450 superfamily (CYPs) (Rossi et al 2003;Silvestri et al 2003;Yuan et al 2008), UDP-glucuronosyltransferases (UGTs) (Vogel et al 2001;Wang et al 2004), and hemochromatosis (HFE) (Shi et al 2005;Ropero et al 2007;Ezzikouri et al 2008a, b).…”
Section: Introductionmentioning
confidence: 99%
“…The design of the Los Angeles HCC Study has been described previously (12,21). Briefly, cases were newly diagnosed HCC patients of black, Hispanic or non-Hispanic white Americans residing in Los Angeles County who were between 18 and 74 years of age at diagnosis from January 1984 through December 2001.…”
Section: Participantsmentioning
confidence: 99%